Antenas impressas de faixa larga utilizando a geometria multifractal do pente de cantor - Santos, Ma?ra Gon?alves (2014)
This work presents the development of printed antennas using the multifractal geometry of the Cantor?s comb. In this configuration, the models use different ratios in each iteration of the fractal and allow operation in multiple frequency bands, with different results from those achieved under traditional iteration conditions. We discuss changes in order to extend the op-erating range around the resonance conditions. Along the development, the proposed struc-tures were simulated with HFSS? software and then some models were tested in laboratory. We analyze characteristics related to the reflection coefficient, irradiation patterns, gain, di-rectivity and radiation efficiency of the antennas. The prototypes were made of glass fiber FR4 and polytetrafluoroethylene laminates. It is proposed a compact model with dimensions of 76mm?38mm?0.9mm which performs within acceptable limits in the range between 3GHz and 20GHz